The causal relationship between education, health and health related behaviour: Evidence from a natural experiment in England - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2010)
I exploit exogenous variation in the likelihood to obtain any sort of academic degree between January- and February-born individuals for 13 academic cohorts in England. For these cohorts compulsory schooling laws interacted with the timing of the CGE and O-level exams to change the probability of obtaining an academic degree by around 2 to 3 percentage points. I then use data on individuals born in these two months from the British Labour Force Survey and the Health Survey for England to investigate the effects of education on health using being February-born as an instrument for education. The results indicate neither an effect of education on various health related measures nor an effect on health related behaviour, e.g., smoking, drinking or eating various types of food.
Keywords: I12; I20; 330; education; health; socio-economic gradient; education gradient; Bildungsniveau; Gesundheit; Gesundheitsvorsorge; Großbritannien